2012
DOI: 10.4236/jct.2012.31011
|View full text |Cite
|
Sign up to set email alerts
|

<i>In Vitro</i> Investigation of DNA Damage Induced by the DNA Cross-Linking Agents Oxaliplatin and Satraplatin in Lymphocytes of Colorectal Cancer Patients

Abstract: Exposure to toxic chemicals, especially chemotherapeutic drugs, may induce several DNA lesions, including DNA interstrand crosslinks. These crosslinks are considered toxic lesions to the dividing cells since they can induce mutations, chromosomal rearrangements, and cell death. Many DNA interstrand crosslinks lesions can be generated by platinum-based chemotherapeutic agents. Satraplatin is a novel orally administered platinum-based chemotherapeutic agent. In the present study, we investigated DNA interstrand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 63 publications
1
4
0
Order By: Relevance
“…Indeed, in vitro DNA cross-link studies showed a significant and concentration-dependent increase in cross-linking activity for 2 PEI30 (up to 50% in relation with the untreated control). The effects were more pronounced than for oxaliplatin (33%, which agreed well with literature data). , …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Indeed, in vitro DNA cross-link studies showed a significant and concentration-dependent increase in cross-linking activity for 2 PEI30 (up to 50% in relation with the untreated control). The effects were more pronounced than for oxaliplatin (33%, which agreed well with literature data). , …”
Section: Resultssupporting
confidence: 91%
“…The effects were more pronounced than for oxaliplatin (33%, which agreed well with literature data). 47,48 We also performed experiments to correlate apoptosis with the production of Reactive Oxygen Species (ROS) in mitochondria, which is associated with a decrease of their normal respiratory activity. 49 We showed that apoptosis is correlated with the induction of a dose-dependent ROS production and an increased number of cells with inactive mitochondria (Figures 8, S4,5) similar to staurosporine, a compound known to affect ROS production and, thus, used as a reference.…”
Section: ■ Introductionmentioning
confidence: 99%
“…2427 The assay investigates the extent of drug-induced DNA crosslinking in individual cells by visualizing and quantifying DNA migration following exposure to DNA damaging agents. 25 The study examined the electrophoretic mobility of DNA from individual cells first treated with MC , Me-AZM , or H-AZM and then subsequently treated with hydrogen peroxide.…”
Section: Resultsmentioning
confidence: 99%
“…This leads to a decreased tail length when compared to cells treated with hydrogen peroxide alone. 24,27 A smaller value for the “tail extent moment”, which is calculated by multiplying tail length by the measured amount of DNA in the tail, 24,25 is indicative of increased DNA interstrand, intrastrand, or DNA-protein crosslinks.…”
Section: Resultsmentioning
confidence: 99%
“…13) In addition, it is also associated with rare cases of ototoxicity 14,15) and hepatotoxicity. 16,17) It has also been reported that highly toxic DNA lesions are caused by oxaliplatin based therapy at the cellular level 18) and may result in DNA damage and therefore higher risk for development of secondary malignancies. 19) In fact, there have been a few cases of secondary acute leukemia reported with oxaliplatin-based therapy.…”
Section: Introductionmentioning
confidence: 99%